Manajemen Pembiayaan Pendidikan di Sekolah Dasar Negeri 4 Ngadirejo Kartasura - Isnaini Maratus Sholihah; Zainab Alqudzi; Suyatmini (Program Studi PGSD STKIP PGRI Banjarmasin, 2023)
In the implementation of education, financing is a potential that greatly determines the quality of human resources and is an inseparable part of the management of educational administration. This study aims to determine: 1) Management of education financing at SDN Ngadirejo 04, 2) Obstacles faced in managing education financing at SDN Ngadirejo 04. This research uses a qualitative descriptive analytical approach. Data collection methods are observation, interviews and documentation. The results of the study show that the process of managing education financing at SDN Ngadirejo 04 goes through the stages of budgeting, budget use, financial records, financial reporting, and financial audits. Constraints and solutions faced include: Delays in the disbursement of BOS funds. The solution is to look for bailouts, the need for student budgets that are not included in the BOS and incidental SPJ funds. The solution is to work together and cooperate with the Committee. BOS funds are not enough to organize the development of facilities and infrastructure. The solution is to submit a proposal for assistance to the Sukoharjo district education office.